Peran Bank Syariah dalam Mendukung Ekonomi Berkelanjutan - Akifah Fakhira, Dhia; Sabila Utami, Meisyah; Wulandari, Afifah; Aryanti, Aryanti (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to explore the role of Islamic banks in supporting sustainable economic development, focusing on the alignment between Sharia values and sustainability principles, the strategies adopted, and the challenges and opportunities encountered. The findings reveal that core Sharia principles such as justice, social responsibility, and environmental stewardship are inherently aligned with the goals of sustainability. However, a significant challenge lies in the limited operational understanding of sustainability concepts and the lack of supportive regulations that recognize the unique role of Islamic banks in green financing. Despite these constraints, there is vast potential for Islamic banks to expand their contribution through innovative green financial products, the strategic utilization of Islamic social funds (e.g., zakat and waqf), and multi-stakeholder collaborations. The study recommends that future research adopt a mixed-methods approach combined with in-depth case studies to gain a more comprehensive understanding of the tangible impact Islamic banking can have on sustainable economic development.